Exploring Values Orientation to build Green Loyalty: the Role of Egoistic, Supply Chain Management, and Biospheric - Erna S. Imaningsih; Prijono Tjiptoherijanto; Ignatius Heruwasto; Daniel Tumpal H. Aruan (International Journal of Supply Chain Management, 2020)
Abstract- The purpose of this paper is to explore the impact of eight dimensions of green supply chain management (GSCM) on economic, environmental and social performance, which are the three dimensions of corporate sustainability. This study aims to examine and analyze the influence of values orientation which consists of egoistic, supply chain, and biospheric towards green loyalty. This research is empirical research through questionnaire survey method distributed to 402 consumers who have experience buying green brands in Indonesia. With SEM data analysis tool. The results show that egoisitic and supply chain have a positive effect on green loyalty, while altruistic does not affect green loyalty.